A Review on Remdesivir: A Possible Promising Agent for the Treatment of COVID-19 - Hashemian SM; Farhadi T; Velayati AA (Dove Medical Press, 2020)
Seyed MohammadReza Hashemian,1,2 Tayebeh Farhadi,2 Ali Akbar Velayati2 1Clinical Tuberculosis and Epidemiology Research Center, National Research Institute of Tuberculosis and Lung Disease (NRITLD), Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Chronic Respiratory Diseases Research Center (CRDRC), National Research Institute of Tuberculosis and Lung Diseases (NRITLD), Shahid Beheshti University of Medical Sciences, Tehran, IranCorrespondence: Tayebeh FarhadiChronic Respiratory Diseases Research Center (CRDRC), National Research Institute of Tuberculosis and Lung Diseases (NRITLD), Shahid Beheshti University of Medical Sciences, Tehran, IranTel/ Fax +982126109931Email tayebehfarhadi@yahoo.comAbstract: The novel coronavirus 2019 (2019-nCoV), formally named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a novel human infectious coronavirus. The disease caused by SARS-CoV-2 is named COVID-19. Development and manufacturing of specific therapeutics and vaccines to treat COVID-19 are time-consuming processes. At this time, using available conventional therapeutics along with other treatment options may be useful to fight COVID-19. In different clinical trials, efficacy of remdesivir (GS-5734) against Ebola virus has been demonstrated. Moreover, remdesivir may be an effective therapy in vitro and in animal models infected by SARS and MERS coronaviruses. Hence, the drug may be theoretically effective against SARS-CoV-2. Remdesivir is a phosphoramidate prodrug of an adenosine C-nucleoside. By entrance into respiratory epithelial cells in human, the prodrug is metabolized to a nucleoside triphosphate as the active form. The nucleoside analog inhibits the viral RNA-dependent RNA polymerase (RdRp) by competing with the usual counterpart adenosine triphosphate (ATP). The nucleoside analog is incorporated into the generating RNA strand and causes a delayed stop in the viral replication process. Knowledge about the potential efficacy of remdesivir against coronaviruses has been restricted to in vitro studies and animal models. However, information related to COVID-19 is rapidly growing. Several clinical trials are ongoing for the management of COVID-19 using remdesivir. In this study, characteristics of remdesivir and its usage for treatment of COVID-19 are reviewed based on an electronic search using PubMed and Google Scholar.Keywords: remdesivir, COVID-19, SARS-CoV-2, RNA-dependent RNA polymerase